Love, Incorporated - Martin, Adrienne M. (Ethical theory and moral practice, 2015)
In this paper, I outline a Kantian moral psychology and use it to generate an analysis of the emotional attitude, love. At the heart of this moral psychology is a distinction between rational and subrational motives, and the thesis that interpersonal emotional attitudes like love are governed by a norm of respect. I show how an analysis of love that relies on this moral psychologywhich I call the incorporation conception of lovetightly fits with paradigmatic cases of romantic love, reveals both the continuities and differences between romantic and other forms of love, and also explicates our ambivalence about certain cases. Finally, I argue that this analysis, although it sees love as essentially a bundle of volitions, has the resources to respond to both David Vellemans and Niko Kolodnys critiques of volition-based analyses of love. Taken as a whole, the discussion provides an argument for both this analysis of love and the moral psychology it presupposes.